Credit Gaps for Financing Micro-enterprises: The Arab Republic of Egypt Case - Wagdi, Osama; Albanna, Hatem (The Arab Journal of Administration, 2025)
The study investigated the credit gaps for financing micro-enterprises in the Arab Republic of Egypt, adopting the descriptive analytical approach through a quantitative analysis of both the demand and supply sides of this type of financing, in addition to a qualitative analysis of the attitudes of stakeholders. The study concluded that according to the quantitative analysis of the credit gaps for financing micro-enterprises during the period 2016-2020, there was a variation in the credit gaps based on the supply side (the three categories of NGOs vs. the microfinance companies), and an addition to the variation in the credit gaps based on the demand side (commercial/agricultural/service/productive), whether at the level of the number of beneficiaries, credit balances, or the average share of one beneficiary at a significant level (1%). According to qualitative analysis, which included a sample of 386 individuals, based on inferential analysis, concluded that the stakeholders’ attitudes towards the importance of microfinance obstacles varied, The same applies to developing microfinance practices. Finally, mechanisms to reduce the credit gap from the supply side at a significant level (1%). On the other hand, there are similar attitudes towards mechanisms to reduce the credit gap on the demand side. Thus, it becomes clear that there are multiple credit gaps for financing micro-enterprises in the Arab Republic of Egypt.